49 Prescriber behaviors that could be targeted for change: an analysis of behaviors demonstrated during the prescribing process. (25th October 2019) - Aseeri, Mohammed; Bannan, Douha F; AlAzmi, Aeshah; Tully, Mary P
Abstract : Background: The prescribing process for children with cancer is complex, and errors can occur at any step. As a result, many interventions have been used to reduce errors. However, few of them have been designed based on an understanding of the prescriber behavior that can lead to errors. In order to design effective behavior change interventions, it is first important to understand the prescribing process and identify prescriber behaviors that could be targeted for change. Methods: This study used two sequential phases. First, the prescribing process was observed and then described using the hierarchical task analysis (HTA) method. Second, prescriber tasks were analyzed using the behavior change wheel (BCW) approach to identify promising behaviors for change. These identified behaviors were prioritized based on information collected from focus groups with prescribers and chart review of errors made in the ward. The hospital's Institutional Review Board approval has been granted. Results: The HTA results showed that the prescribing process was complex and involved multiple tasks performed in varying orders. Applying the BCW identified 32 candidate behaviors for potentially reducing prescribing errors. However, after prioritizing these behaviors, only two emerged as promising candidate behaviors for intervention: writing drug indications at the time of prescription and using a predefined order sentence when ordering medications. Conclusion: Applying the HTA and BCW methods was helpful in identifying potential behaviors for change. Having identified promising behaviors, future work could explore what needs to change with respect to individuals and their work environments to achieve the desired change in these identified behaviors.